2013
DOI: 10.1096/fj.12-205054
|View full text |Cite
|
Sign up to set email alerts
|

EphB2 isolates a human marrow stromal cell subpopulation with enhanced ability to contribute to the resident intestinal cellular pool

Abstract: To identify human bone marrow stromal cell (BMSC) subsets with enhanced ability to engraft/contribute to the resident intestinal cellular pool, we transplanted clonally derived BMSCs into fetal sheep. Analysis at 75 d post-transplantation showed 2 of the 6 clones engrafting the intestine at 4- to 5-fold higher levels (5.03±0.089 and 5.04±0.15%, respectively) than the other clones (P<0.01), correlating with the percentage of donor-derived Musashi-1(+) (12.01-14.17 vs. 1.2-3.8%; P<0.01) or leucine-rich repeat-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…Although it remains controversial, because EphB/EphrinB contactdependent repulsion behavior appears during the modulation of cell sorting [59], it appears that OA-induced EphB2 expression can impart the ability to migrate to wound sites in UCB-MSCs. A high level of EphB2 expression is reported to enhance the homing and engraftment of human bone marrow stromal cells [15]. Our results indicate that OA-induced EphB2 expression is important for UCB-MSC migration both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Although it remains controversial, because EphB/EphrinB contactdependent repulsion behavior appears during the modulation of cell sorting [59], it appears that OA-induced EphB2 expression can impart the ability to migrate to wound sites in UCB-MSCs. A high level of EphB2 expression is reported to enhance the homing and engraftment of human bone marrow stromal cells [15]. Our results indicate that OA-induced EphB2 expression is important for UCB-MSC migration both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 51%
“…It has also been reported that Ephs play significant roles in a wide range of stem cell behaviors [9]. Moreover, Eph/Ephrin signaling contributes to the recruitment of MSCs into injury sites via the promotion of MSC migration [14,15]. Although the expression patterns of Ephs during developmental progresses have been described, the regulatory mechanism of Ephs has not been fully elucidated in stem cells [16].…”
Section: Introductionmentioning
confidence: 99%
“…A different strategy is to select a subpopulation of MSCs within the bone marrow that expresses high levels of EphrinB2. This subpopulation has an increased migration capacity to intestinal injury areas, and as a consequence, these MSCs would help to improve healing of intestinal injury [42] . Once MSCs engraft in the intestinal damaged tissue they can proliferate and transdifferentiate into intestinal stem cells, or secrete cytokines and growth factors that will promote the proliferation and differentiation of intestinal stem cells in order to repair the injured areas of the intestinal tissue [43] .…”
Section: Mesenchymal Stem Cell Transplantationmentioning
confidence: 99%
“…Another approach is based on the selection a subpopulation of BM-MSCs expressing high levels of EphrinB2. This MSC subset has increased migratory capacity to areas of intestinal injury, this peculiarity being expected to improve the healing process [117]. Finally, Levy et al [118] used messenger RNA transfection to generate BMMSCs that simultaneously express molecules mediating rolling of neutrophils (P-selectin glycoprotein ligand-1 and sialyl-Lewis X) to rapidly target inflamed tissues, and the potent immunosuppressive cytokine interleukin-10 (IL-10), which is not inherently produced by MSCs.…”
Section: Unanswered Questions and Future Perspectivesmentioning
confidence: 99%